Can Channel-Forming Antibiotics In Complex with Carriers Provide Enhanced Muscle Activity? - T. P. Taghi-Zada; Kh. M. Kasumov (Антибиотики и Химиотерапия, 2021)
The presented review and experimental work provides the data regarding the selective permeability of lipid and cell membranes for ions and organic compounds under the influence of channel-forming polyene compounds with a known molecule structure. It has been shown that the polyene antibiotic levorin А2 with an aromatic structure affects a number of physicochemical parameters of lipid membranes. It was established that the permeability of lipid and cellular membranes for monovalent cations, as well as for monosugar and other neutral molecules increases under the influence of a levorin of А2. The biological activity of levorin А2 and the rate of delivery of molecules to the membranes depend on the surface tension and substrate environment of the membranes. It has been shown that in combination with levorin, dimethyl sulfoxide, and citral, the surface tension of the aqueous solutions surrounding the membrane decreases by half. Comparative data on levorin А2 effects on lipid membranes and muscle cell membranes are presented. It is assumed that levorin А2, being a channel-forming compound, can induce the formation of additional permeability channels in the membranes of muscle cells and, with intense muscle activity, enhance the transfer of cation and energy-dependent substrates through the membranes.